Accelerated lung aging: a novel pathogenic mechanism of chronic obstructive pulmonary disease (COPD). (22nd July 2009) - MacNee, William
Abstract : An enhanced or abnormal inflammatory response to the lungs to inhaled particles and gases, usually from cigarette smoke, is considered to be a general pathogenic mechanism in COPD (chronic obstructive pulmonary disease). Activation of leucocytes and the development of oxidant–antioxidant and protease–anti-protease imbalances are thought to be important aspects of this enhanced inflammatory response to cigarette smoke. The mechanisms involved in the perpetuation of the inflammatory response in the lungs in patients who develop COPD, even after smoking cessation, are not fully established and are key to our understanding of the pathogenic mechanisms in COPD and may be important for the development of new therapies. There is a relationship between chronic inflammatory diseases and aging, and the processes involved in aging may provide a novel mechanism in the pathogenesis of COPD. There is good evidence linking aging and COPD. During normal aging, pulmonary function deteriorates progressively and pulmonary inflammation increases, accompanied in the lungs by the features of emphysema. These features are accelerated in COPD. Emphysema is associated with markers of accelerated aging in the lungs, and COPD is also associated with features of accelerated aging in other organs, such as the cardiovascular and musculoskeletal systems. Cigarette smoke and other oxidative stresses result in cellular senescence and accelerate lung aging. There is also evidence that anti-aging molecules such as histone deacetylases and sirtuins are decreased in the lungs of COPD patients, compared with smokers without COPD, resulting in enhanced inflammation and further progression of COPD. The processes involved in accelerated aging may provide novel targets for therapy in COPD. The present article reviews the evidence for accelerated aging as a mechanism in the pathogenesis of COPD.